Ordinary measures of attention to diversity? - Polo Martínez, Ignacio (Avances en Supervisión Educativa, 2013)
The teacher of a certain subject area is able to program and justify the reinforcement-support plan that is being applied to a student who has failed the first evaluation? 84% of the academic performance achieved by the OECD countries, according to Mackinsy & Company (2012), reveals that it depends, among other factors, on the level of education of the teaching staff and the quality of the educational processes. The key to achieving an improvement of the educational system is to select carefully those educational measures that are appropriate for the level of performance of our students and implement them with perseverance and discipline in individualized teaching practice. One of those measures to be developed should be the improvement of attention to the ordinary diversity of our students. Attention to diversity is a need that will encompass all educational stages and all students. LOE 2/2006 of May 3 tries to contemplate the diversity of students as a principle and not as a measure that corresponds to the needs of a few.This principle is not always present in Primary and Secondary schools. The current educational system proposes a series of educational programs and interventions of specialists oriented to the attention to the diversity that, being indispensable, conceal, in some cases, a lack of individual responsibility and of pedagogical preparation of the teacher in determining and applying the measures of ordinary support and reinforcement before the first deficiencies detected in the essential learning of the students. Through this article it is intended to provide the teacher with some keys to be taken into account for, from the essential learning (content and minimum evaluation criteria required), determine individualized reinforcement-support plans for those students who begin to present difficulties in their process Learning.